2019
DOI: 10.1177/1073191119851563
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Analysis of the Social Anxiety Scale for Adolescents Among Youth With Autism Spectrum Disorder: Caregiver–Adolescent Agreement, Factor Structure, and Validity

Abstract: Social anxiety is common among adolescents with autism spectrum disorder (ASD). An ongoing challenge for both research and clinical practice in ASD is the assessment of anxious symptomatology. Despite its widespread use in samples of youth with ASD, the Social Anxiety Scale for Adolescents (SAS-A) has not received psychometric evaluation within this population; thus, the validity of its use in research and clinical practice for ASD remains unclear. The present study conducted a psychometric analysis of caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 84 publications
2
9
0
Order By: Relevance
“…Items from both the WEMWBS and SDQ were also distinct to those items reporting on FNE, thus further highlighting how FNE might be a key underlying or maintaining factor that can increase an individual's vulnerability specifically to social anxiety. Evidence supporting construct invariance of FNE as measured by SAS-A is also concordant with one recent study that examined psychometric properties of the SAS-A when completed by autistic youths and their caregivers (Schiltz et al 2019). Compared to items that loaded onto the SAD factor which described both generalised social anxiety and anxiety in new social situations, the magnitude of the FNE subscale's factor loadings showed greater consistency between autistic young people and their caregivers.…”
Section: Social Anxiety Symptomssupporting
confidence: 81%
“…Items from both the WEMWBS and SDQ were also distinct to those items reporting on FNE, thus further highlighting how FNE might be a key underlying or maintaining factor that can increase an individual's vulnerability specifically to social anxiety. Evidence supporting construct invariance of FNE as measured by SAS-A is also concordant with one recent study that examined psychometric properties of the SAS-A when completed by autistic youths and their caregivers (Schiltz et al 2019). Compared to items that loaded onto the SAD factor which described both generalised social anxiety and anxiety in new social situations, the magnitude of the FNE subscale's factor loadings showed greater consistency between autistic young people and their caregivers.…”
Section: Social Anxiety Symptomssupporting
confidence: 81%
“…As previously discussed, measurement of anxiety in autism has been found to be complex [Kerns, Rump, et al, ; Mazefsky et al, ; South & Rodgers, ; White et al, ]. Only a handful of measures of anxiety have received comprehensive psychometric evaluation using autism samples [e.g., Magiati et al, ; Schiltz et al, under review; van Steensel, Deutschman, & Bögels, ]. Clinical interviews are generally accepted as more robust than questionnaire measures, yet only one study returned in this review utilized this approach [Hollocks et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…For symptom severity, it is recommended that measures that have been psychometrically evaluated and found to be reliable and valid in autism samples should be utilized. This includes the Social Anxiety Scale [Schiltz et al, under review] and the Screen for Child Anxiety‐Related Emotional Disorders [van Steensel et al, ]. The Spence Child Anxiety Scale was recently evaluated using a large, international sample and results indicated that it is not an ideal tool for use in autism [Magiati et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have provided substantial evidence on the important contribution of PKMζ in BLA to the genesis of anxiety, in both normal mice and ASD model mice. Mounting clinical evidences indicate the prominent presence of anxiety in ASD patients (Ishimoto et al, 2019; Schiltz et al, 2019). We found that reducing PKMζ activity with ZIP peptide reduces anxiety in P35 VPA mice but not in P70 VPA mice.…”
Section: Discussionmentioning
confidence: 99%